Resistance selection of local sorghum varieties in East Nusa Tenggara, Indonesia against Rhizoctonia solani - EWINDA ISENSI FENI; SRI KASMIYATI; V. IRENE MEITINIARTI (Society for Indonesian Biodiversity, 2023)
Abstract. Feni EI, Kasmiyati S, Meitiniarti VI. 2023. Resistance selection of local sorghum varieties in East Nusa Tenggara, Indonesia against Rhizoctonia solani. Biodiversitas 24: 5309-5318. Sorghum is a multifunctional crop that can be used as an alternative food for the people of East Nusa Tenggara. However, one of the challenges in cultivating sorghum in this region is the presence of the Rhizoctonia solani pathogen. This fungus causes a devastating root rot disease in sorghum crops, resulting in loss of crop yields and potentially disrupting food security in the region. Using resistant varieties is one of the most effective ways to prevent the growth of R. solani biologically. Therefore, it is important to study the resistance of local sorghum varieties. The purpose of this study was to determine different sorghum varieties' resistance responses to the R. solani fungus that causes root rot disease. This study used a completely randomized design (CRD) with 2 levels of treatment: the treatment of sorghum varieties and the treatment of fungi inoculums, which were inoculated separately and simultaneously. Each treatment was repeated 3 times. Observations and data collection were carried out on the 7th day, and some of the parameters observed included germination percentage, radicle length, coleoptile length, sprout length, GTI value, and disease incidence value. The sorghum variety with the highest resistance value was found in the red variety. This red variety had a disease incidence value of 63.3%, much lower than the other four test varieties. These results provide important insights for developing a more root rot disease-resistant local sorghum plant variety.